1998
DOI: 10.1111/j.1365-2621.1998.tb15841.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Oxidation of Menhaden Oil as Affected by Emulsifiers

Abstract: The ability of Tween 20 and whey protein isolate (WPI) to influence lipid oxidation was investigated by evaluating the effects of emulsifier concentration and physical location on iron-catalyzed oxidation of emulsified Menhaden oil. Addition of Tween 20 or WPI to the aqueous phase of a 0.5 wt% Tween 20 stabilized emulsion increased lipid oxidation as determined by both thiobarbituric acid reactive substances (TBARS) and lipid peroxides. Tween 20 (2.0 wt%) and WPI (0.05-1.0 wt%) combinations inhibited TBARS for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 18 publications
4
98
2
3
Order By: Relevance
“…In emulsions made with Tween 20, a nonionic surfactant, the rate of lipid oxidation was faster at pH 3 than at 7 [8]. Similarly, in lycopene emulsions stabilized with SDS the oxidation rates were higher at pH 4 and below [9].…”
Section: Introductionmentioning
confidence: 84%
“…In emulsions made with Tween 20, a nonionic surfactant, the rate of lipid oxidation was faster at pH 3 than at 7 [8]. Similarly, in lycopene emulsions stabilized with SDS the oxidation rates were higher at pH 4 and below [9].…”
Section: Introductionmentioning
confidence: 84%
“…Similarly, an excess of Tween 20 added to the aqueous phase of a rapeseed oil-in-water emulsion delayed lipid oxidation and decreased the reaction rate (Berton et al 2011). Conversely, Donnelly et al (1998) noticed that the addition of Tween 20 in the aqueous phase of a Tween 20-stabilized emulsion increased lipid oxidation as determined by both lipid peroxides and TBARS (thiobarbituric acid reactive substances) values. One may suspect that this puzzling influence of surfactant micelles is due to the fact that those micelles do not solubilize only LOOHs.…”
Section: Figurementioning
confidence: 99%
“…Emulsions with XG may suppress the lipid oxidation by chelation of iron between two side chains with a pyruvate residue. Several authors (Mei, McClements, Wu, & Decker, 1998a;Donelly, Decker, & McClements, 1998;Sun et al, 2007;Faraji, McClements, & Decker, 2004) reported the inhibition of the lipid oxidation by chelation of iron and therefore inactivating the peroxyl radicals. Emulsions containing XG/LBG mixtures ( Fig.…”
Section: Effect On Oxidative Stability Of the Emulsionsmentioning
confidence: 99%